Environmental regulation and the location of polluting industries - Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
Does international tax competition in the environmental field lead to undesirably low levels of environmental regulation and to unacceptable disruptions of environmental quality? The paper tries to answer this question in a non-competitive partial-equilibrium framework. There is one firm that wishes to establish a plant in one of n countries. The paper shows that tax competition may lead to emission taxes that are either too low or too high. They may be so high that the investment is not undertaken although this would be optimal if the countries cooperated. On the other end of the spectrum, a scenario in which taxes are driven to zero becomes possible if there are substantial transfrontier pollution effects.
Keywords: 330; Umweltabgabe; Steuerwettbewerb; Betriebliche Standortwahl; Multinationales Unternehmen; Theorie